ECONOMIC GROWTH DETERMINANTS OF ASEAN COUNTRIES: BEFORE AND AFTER THE COVID-19 PANDEMIC - Hasanah, Uswatun; Joko Widodo; Amin Pujiati (Business and Economic Analysis Journal, 2025)
Economic growth in ASEAN countries in recent decades has attracted the attention of many parties, both academics and practitioners. This study evaluates the various factors contributing to ASEAN countries' economic growth. The factors analyzed include human development index, exports, foreign investment, exchange rates, population, and dummy variables (before and after) the COVID-19 pandemic. This research uses a quantitative approach with the object of research, namely ASEAN countries, from 2018 to 2022. Data sources from the World Bank, the National Statistics Bureau, and other credible sources. Based on the results of the analysis, the human development index and foreign investment have a positive and significant effect on economic growth. In contrast, exports, exchange rates, population, and dummy variables positively and insignificantly impact economic growth. Suggestions that can be given are that each country must pay attention, especially to policies on exports, which include duties, excise, and taxes. In addition, a large quantity of population does not guarantee the success of a nation, therefore it is necessary to pay attention to the quality side as well, this can be done by paying attention to the education side which correlates with the demand for labor, so that there is no imbalance between demand and supply of labor.